2012
DOI: 10.1080/19439342.2012.720995
|View full text |Cite
|
Sign up to set email alerts
|

Benefits trickling away: the health impact of extending access to piped water and sanitation in urban Yemen

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 34 publications
(22 reference statements)
1
37
0
Order By: Relevance
“…17 Interestingly, the three infrastructure variables-piped water, flush toilets, and electricity-all show very weak relationships, suggesting their relationship to nutrition is not very robust. Although we suspect that these weak relationships partly stem from the fact that these factors really are less important drivers of nutritional change, it could well be that piped water and flush toilets are very poor proxies for water and sanitation quality (Klasen, Tobias, Kristina, & Johannes, 2012;Smith & Haddad, 2002). Table 5 shows two regressions which confirm this pattern of bivariate results in a multivariate context (because of sample size constraints, the country trend effects in these regressions are dropped).…”
Section: Social and Infrastructural Dimensions Of Nutritional Changesupporting
confidence: 55%
“…17 Interestingly, the three infrastructure variables-piped water, flush toilets, and electricity-all show very weak relationships, suggesting their relationship to nutrition is not very robust. Although we suspect that these weak relationships partly stem from the fact that these factors really are less important drivers of nutritional change, it could well be that piped water and flush toilets are very poor proxies for water and sanitation quality (Klasen, Tobias, Kristina, & Johannes, 2012;Smith & Haddad, 2002). Table 5 shows two regressions which confirm this pattern of bivariate results in a multivariate context (because of sample size constraints, the country trend effects in these regressions are dropped).…”
Section: Social and Infrastructural Dimensions Of Nutritional Changesupporting
confidence: 55%
“…Piped water systems are a new phenomenon in rural Bangladesh, and there is so far little documented experience on either the financial sustainability of such systems, or the quality of water they are able to deliver. Experiences from other countries suggests that intermittently operated piped water schemes are vulnerable to fecal contamination, and do not necessarily deliver water which is safer than point sources (Klasen et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, this overall estimate included non-interventions that were previously ineligible, such as hospital-based case-control studies [84][85][86]. Sixteen studies were found that measured the effect of a sanitation intervention [21,22,24,49,50,55,[73][74][75][76][77][78][79][80][81][82]. In a sub-analysis, these intervention studies were found to reduce diarrheal disease by 23% (OR = 0.77, 95% CI 0.66, 0.91).…”
Section: Jung Et Al 2017mentioning
confidence: 99%
“…However, this estimate still includes school-based interventions, which likely follow unique transmission dynamics, and three sewerage studies that possibly drive the observed overall effect of sanitation interventions. In this update, eight new eligible sanitation studies were identified and added to the 11 studies from Wolf et al 2014 [19,21,22,24,[48][49][50][51][52][53]55,58,[77][78][79][87][88][89][90]. Four estimates were extracted from Interventions that led to sanitation coverage of <75% reduced diarrhea by an average of 24% (RR = 0.76, 95% CI = 0.51, 1.13), and those that led to coverage >75% reduced diarrhea by 45% (RR = 0.55, 95% CI 0.34, 0.91).…”
Section: Jung Et Al 2017mentioning
confidence: 99%
See 1 more Smart Citation